الإطار الشرعي لاستخدام التحيزات المعرفية في الاقتصاد السلوكي: Sharia framework for using cognitive biases in behavioral economics - Hussein, Alaaeldin; Chourana, Mohamed (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث وفي ظل التحولات الكبرى التي يمر بها العالم في شتى المجالات، وفي القلب منها التحولات الإقتصادية، نرى الشريعة الإسلامية بخلودها ومرونتها تستوعب كل المستجدات، وحاضرة وبقوة لتقول كلمتها، حيث أنها منذ صدر الإسلام وضعت المعايير والأطر والمبادئ التي يسير عليها العباد، بما يحقق غايات التشريع، ويراعي مصالحهم من غير جمود ولا عنت، مع إعطاء كل ذي حق حقه. ولذلك هدفت هذه الدراسة إلى موقف الشريعة الإسلامية من استخدام الاقتصاد السلوكي، وتوجيه التحيزات المعرفية في الاقتصاد، وأقوال الفقهاء في ذلك، وهل لهذا العلم أساس في الشرع؟ ، وما الأخلاق والقيم والمبادئ التي يجب الوقوف عليها عند استخدام ذلك؟ ، وكيف يمكن - من منظور شرعي- ترشيد السلوك الإستهلاكي للمجتمعات الإسلامية وترشيد استخدام موارد الأمة الإسلامية ؟ ABSTRACT Considering the major transformations the world is witnessing in various fields—foremost among them economic changes—the Islamic Sharia, with its timelessness and flexibility, remains capable of encompassing all new developments. It stands strong and present to offer its guidance. Since the early days of Islam, Sharia has established the standards, frameworks, and principles by which people are to live, in a way that fulfills the objectives of legislation and takes their interests into account—without rigidity or hardship—while giving everyone their due rights. Therefore, this study aims to explore the position of Islamic Sharia regarding the use of behavioral economics, the guidance of cognitive biases in economic behavior, the views of jurists on this matter, and whether this field has a basis in Islamic law. It also examines the ethics, values, and principles that must be considered when applying such concepts, and how— from a Sharia perspective—consumer behavior can be regulated within Islamic societies and how the resources of the Muslim Ummah can be properly managed.